Multivariate analysis applied to the supply of liquefied petroleum gas (LPG) in Peru - Adaniya Higa, Beatriz (2020)
This article provides a brief analysis on energy supply security, focusing mainly on the variables related to the supply of liquefied petroleum gas (LPG) within the Peruvian market. Furthermore, via the use of real data, principal component analysis (PCA), one of the most common multivariate techniques, is explained and illustrated, whose result indicates that a correlation exists between the analyzed variables.